Modelling and simulation of optical transmitter for 5G passive optical networks - Sura Adil Abbas; Jaafar A. Aldhaibani (Institute of Advanced Engineering and Science, 2023)
5G is altering the communications future. The 5G literature focuses on wireless and radio technology, but fiber optics play a crucial supporting role in signal transmission to and from the next generation of base stations (BSs) that will serve customers. With the increasing bandwidth requirements of 5G ultra-high-speed applications, passive optical networks (PONs) are the optimal solution. Targeting long-reach 5G PONs, an integrated, high-speed, and cost-effective optical transmitter circuit was constructed and tested. This engine can be combined into a 5G-compliant optical transceiver module. For the purpose of validating the engine performance, a theoretical analysis and an OptiSimTM-based design simulation model are carried out. Bit error rate (BER), phase-shifting, and eye diagram were all taken into account when analyzing the transmitter performance. The article findings validate the optical transmitter design. The design is cost-effective and requires no extra components, such as a filter.